2014
DOI: 10.7205/milmed-d-14-00164
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training Risk Factors for Musculoskeletal Injury in Female Soldiers

Abstract: Musculoskeletal injuries (MSIs) result in the most medical encounters, lost duty days, and permanent disability. Women are at greater risk of injury than men and physical training is the leading cause of injury. The purpose of this study was to investigate the demographic, body composition, fitness, and physical training risk factors for injuries in female Soldiers serving in garrison Army units over the past 12 months. Self-report survey was collected from 625 women. The ankle was the most frequently injured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 81 publications
2
31
0
Order By: Relevance
“…However, uncontrolled excessive exercise may cause many adverse effects. Recent reports have indicated that extreme exercise may induce musculoskeletal injuries, cardiac arrhythmias, and biochemical and histological changes in the liver and pancreas of rats …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, uncontrolled excessive exercise may cause many adverse effects. Recent reports have indicated that extreme exercise may induce musculoskeletal injuries, cardiac arrhythmias, and biochemical and histological changes in the liver and pancreas of rats …”
Section: Introductionmentioning
confidence: 99%
“…2 However, uncontrolled excessive exercise may cause many adverse effects. Recent reports have indicated that extreme exercise may induce musculoskeletal injuries, 3 cardiac arrhythmias, 4 and biochemical and histological changes in the liver and pancreas of rats. 5 Among adolescents, exercise for the purpose of weight loss is rising, which is influenced by increased sociocultural pressures on appearance, as slenderness and muscular V-shaped body are considered the ideal physique.…”
Section: Introductionmentioning
confidence: 99%
“…We observed higher LBP prevalence among respondents with a history of LBP and among those with a history of accidents. Previous studies have reported similar findings and concluded that LBP history is one of the strongest risk factors for developing recurrent LBP in the future [12,14]. Stanton et al [19] reported that 25 to 62 percent of LBP patients experienced recurrent LBP within one to two years' time-frame.…”
Section: Discussionmentioning
confidence: 60%
“…Higher risk for injury has been most consistently demonstrated among Soldiers with lower aerobic fitness levels, cigarette smokers, and those with lower levels of physical activity prior to Army basic combat training (Knapik et al, 2006). The severity of injuries and their impact on military operations are well documented and can be reviewed elsewhere (Marshall et al 2014;Zambraski and Yancosek 2012;Roy et al 2014). …”
Section: Outcomes Of P Process Step Onementioning
confidence: 99%